PEMANFAATAN LIMBAH BATU BATA MERAH DALAM STABILISASI TANAH LEMPUNG - Misbah Misbah; Wikal Sundus (Ensiklopedia of Journal, 2021)
Land is a place to build a foundation or building that supports all the loads of the structure or construction that stands on it, both building construction and road construction. Especially for roads, soil inspection is important so that the road construction that is built can last a long time. In the area of Kampung Baru, Simpang Haru, Sawahan Timur Village, Padang Timur District, the land needs to be researched because the soil condition is less stable, it can be seen by the damage to several infrastructures, especially roads, damage in the form of cracks, potholes to collapse. location. To improve the stability of the soil, research was carried out using a stabilizing agent in the form of red brick waste. The waste red bricks used are those that pass filter no. 200, with the percentage of red bricks in the soil content of 0%, 5%, 7.5% and 10%. The tests carried out consisted of testing the physical properties and mechanical properties of the soil. Testing the physical properties of the soil includes the sieve test no. 200, specific gravity test (Gs), atterberg limit test and sieve test. Meanwhile, testing of mechanical properties includes soil density test, expansion test and expansion pressure. Based on the research that has been done above, it can be concluded that the addition of red brick waste powder can reduce the plasticity, expansion and expansion pressure of clay soil. The best results were achieved by mixing 5% of red brick waste to the dry weight of the soil